EFEKTIVITAS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS DAN MENJAGA TINGKAT LIKUIDITAS (Studi Penelitian Pada KUD “Karya Bhakti” Jombang Tahun 2011-2015) - Nola Rektasiwi Okila; Fransisca Yaningwati; Dwiatmanto Dwiatmanto (Jurnal Administrasi Bisnis, 2016)
The use of net working capital, or working capital is very important for the analyzer internally and externally, in addition to the problem of working capital is closely related to the company's daily operations also indicates the level of security or margin of savety creditors mainly short-term creditors. The purpose of this study was to determine the effective management of working capital at KUD “Karya Bhakti” towards increased profitability and maintain liquidity. Type of research include descriptive using a case study approach. The research location KUD "Karya Bhakti". The data used are primary data and secondary data. Results found indicate that conditions profitability ratio increased cooperation in 2011-2016, showed that KUD "Karya Bhakti" improve the effectiveness of an increase in the use of assets in generating profits. The level of liquidity can be maintained so that KUD "Karya Bhakti" can be said to be good. It is important for the cooperative to streamline the amount of cash, in order to draw up budget cash management were really appropriate for the cooperative in accordance with well finance. It requires management policy in order to manage accounts receivable turnover increased and the number of cooperatives soon paid off at maturity. Keywords :Working capital, Profitability, Liquidity ABSTRAK Penggunaan  net working capital atauI modaIl kerjaI sangat penting bagi penganalisa intern maupun ekstern, disamping masalahImodal kerjaI ini erat hubungannyaI dengan operasiI perusahaanI sehari-hari jugaI menunjukkanI tingkat  keamananI atau marginI of savetyI para krediturI terutama kreditur jangka pendek. Tujuan penelitianI ini adalah untuk mengetahui pengelolaanI modal kerja yang efektifI pada KUD KaryaI Bhakti terhadap peningkatanI profitabilitasI dan menjaga likuiditasnya. JenisI penelitianI yang dilakukan termasuk deskriptifI dengan menggunakanI pendekatanI studiI kasus. Data yang digunakan adalah data primerI dan dataI sekunder. TemuanI menunjukkan bahwaI kondisi rasio profitabilitas koperasi tahun 2011-2016 mengalamiI kenaikan, KUDI “Karya Bhakti” mengalami kenaikanI dalam pengefektifan penggunaan aktivaI dalam menghasilkanI laba. Tingkat likuiditasI dapat dipertahankanI sehingga KUD “Karya Bhakti” dapat dikatakanI baik. PentingI bagi koperasiI untuk mengefektifkan jumlah kas, agar pihak manajemenI menyusunI budget kas yang benar-benar tepat bagi koperasi sesuai dengan well finance.  Perlu penetapanI kebijakan manajemenI dalam mengelolaI piutangI agar perputarannyaI meningkatI dan jumlah piutangI koperasiI segera terlunasiI pada saat jatuh tempo. Kata kunci: Modal kerja, profitabilitas dan likuiditas